Aktivitas Ramuan Daun Salam, Herba Pegagan, Akar Alang-Alang dan Biji Pala pada Tikus Hipertensi yang Diinduksi Prednison dan Garam - Nisa, Ulfatun; Fitriani, Ulfa; Wijayanti, Enggar (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2017)
The prevalence of hypertension in Indonesia was 25,8%. As much as 70% types of hypertensive patients were mild hypertension. There were some medicinal plants contain single formulation could be used for lowering blood pressure but not in a herbal formulation. This study determined the efficacy of antihypertension herbal formulation that consists of Indonesian bay leaves, Centella herbs, blady grass roots and nutmeg seeds. This study was an experimental laboratory research with pre and post-test controlled design, used thirty Sprague-Dawley rats that were classified randomly into five groups (negative control group which didn't have treatment, positive control group which consumed captopril 0,25 mg, and three groups which consumed antihypertension herbal formulation with doses of 0,08 g; 0,16 g; and 0,32 g. The rats were induced by prednisone and NaCl 2,5 % for 21 days. The data were analysed using ANOVA test with CI 95%. After two weeks observation, the results showed that the blood pressure in the negative control group increased, but in the positive control and treatment groups decreased significantly (p=0,001). In conclusion, the herbal formulation could decrease rat's blood pressure